A racionalidade comunicativa como ágora de processos educativos emancipatórios - Medeiros, José Washington de Morais (2011)
This study has as object the technicist logic of the pedagogical acting, based on the communicative rationality. Considering this model of reason concerning the utopia of human emancipation, it is hooked on the theory of the Communicative Action (TCA) by Jürgen Habermas. It contextualizes the invasions to which the educative processes are subjected in the contemporaneity prometed by the inbrication between the systemic and the lived worlds. It aimed at understanding the technicist dynamics of the pedagogical acting under the domains of TCA, starting from the following thesis: the technicist pedagogy is a kind of manifestation of the instrumental rationality present in the world lived within school. Through the hermeneutic method, it went in search of the possibilities of emancipation, going from the rationalization and its three universal spheres: a) culture, through educative processes which found the reevaluation of moral and ethical values formerly established; b)society, through consensual norms that only become valid before intelligible argumentations sensitively inclined to redefinitions; c) personality, through a cognitive development beyond mentalism, passing by the evolution of a moral conscience that elaborates stages of intersubjective relations. As a result of the deadlock of education, it brings the possibility to think how much the communicative rationality has lost spaces for the instrumental rationality, consequently coming up several social pathologies. On account of this, it discusses that natural and public channels of the communicative spaces (language as a medium) are deteriorated by the vehicles placed by the systemic imperatives (money and power as craftsmen) of the Western capitalist society. It perceives that the effects by the colonizations of the instrumental reason in the cognitive, expressive and normative spheres interfere much in social formations, binding the rationalizations of the lived world. Thus, the circumstances brought by the extranatural domains of educations facilitated the coming of a set of impositions at school, since the regeneration of the philosophy based on the subject (hyperindividualism) until the instructive normalizations of the technified educations. Aiming at uncovering the genesis of the educational atrophies, it concludes that the communicative rationality can be understood as a new agora ; a fertile alternative to incite a linguistic overturn in the mediations of the subject, in the interactions with others, with the knowledge, with the images (religious and metaphysical) of the world. It emphasizes that the communicative rationality can subsidize educative processes beyond functional ideologies linearly induced by the tecnification of thinking. A reflexive reason that promotes a sort of educations that is open to the multiple voices of rationality. It ends highlighting that, to strengthen the lived world, the paradigm of the communicative rationality propitiates the progressive development of human competence which, under the idea of emancipator education, the utopia of which one is in search becomes a criterion for social evolution.